2017
DOI: 10.1007/s11259-017-9684-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intramammary infusion of recombinant bovine GM-CSF and IL-8 on CMT score, somatic cell count, and milk mononuclear cell populations in Holstein cows with Staphylococcus aureus subclinical mastitis

Abstract: The effect of intramammary infusion of recombinant bovine granulocyte-macrophage colony-stimulating factor (rbGM-CSF) and interleukin-8 (rbIL-8) on mononuclear cell populations in quarters, somatic cell count (SCC) and the California Mastitis Test (CMT) score were investigated. From the selected cows with naturally occurring Staphylococcus aureus subclinical mastitis, one quarter of each cow were selected for the infusions of rbGM-CSF (400 μg/5 mL/quarter, n = 9), rbIL-8 (1 mg/5 mL/quarter, n = 9), and phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Bovine mastitis is an important and economically relevant disease that affects the dairy industry worldwide (Bar et al, 2011; Gomes and Henriques, 2016). This disease causes large economic losses every year; estimated to be as high as $2 billion/year in the United States alone (Blosser, 1979; Petrovski et al, 2006) These losses are mainly due to reduced milk yield, antibiotic therapy, veterinary services, and the reduced price of culled animals (Blosser, 1979; Kiku et al, 2017). Mastitis is most often an acute or chronic inflammation of the mammary glands caused by bacterial infection and commonly leads to increased SCC, cytokine production, antibody secretion, and bacterial load in milk (De Vliegher et al, 2012; Thompson-Crispi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bovine mastitis is an important and economically relevant disease that affects the dairy industry worldwide (Bar et al, 2011; Gomes and Henriques, 2016). This disease causes large economic losses every year; estimated to be as high as $2 billion/year in the United States alone (Blosser, 1979; Petrovski et al, 2006) These losses are mainly due to reduced milk yield, antibiotic therapy, veterinary services, and the reduced price of culled animals (Blosser, 1979; Kiku et al, 2017). Mastitis is most often an acute or chronic inflammation of the mammary glands caused by bacterial infection and commonly leads to increased SCC, cytokine production, antibody secretion, and bacterial load in milk (De Vliegher et al, 2012; Thompson-Crispi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[23,24]. During mastitis, invasive pathogenic bacteria activates the immune response systems, such as innate immunity [25], cellular immunity [26,27] and humoral immunity [26]. The mucosal immune system is the main site of local non-specific immune function and plays important roles in function of the innate immune system, serving as the first-line of defence against infections [28], which consists of intestinal, respiratory, urogenital mucosa, and the exocrine glands [26].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that cow mastitis has complex traits (clinical and subclinical mastitis) and is affected by multiple factors, including genetic features, nutrition, and hygiene standard, pathogen infections, and seasonal changes. Among them, pathogen infection (Gram-negative, such as Escherichia coli ; Gram-positive, such as Staphylococcus aureus and Streptococcus uberis ) is the main cause of mastitis (813). Therefore, rapid identification of pathogens is critical to determine the symptoms of infection (14).…”
Section: Introductionmentioning
confidence: 99%